The Influence of Psychological Capital and Social Capital on the Entrepreneurial Performance of the New Generation of Entrepreneurs - Wang, Ruoqi; Zhou, Haijun; Wang, Lei (Frontiers in Psychology, 2022)
To enable that the new generation of entrepreneurs can effectively use their own qualities and abilities to improve the level of entrepreneurial performance, and to successfully pass through the entrepreneurial period of the enterprise and achieve longer-term development, the new generation of entrepreneurs is taken as the research object, and firstly, the definition and interaction of psychological capital and entrepreneurial performance are pointed out. Secondly, the questionnaires are designed with reference to the relevant maturity scales, and the reliability, validity analysis, correlation analysis and multiple linear regression analysis of the collected effective questionnaires are carried out through SPSS and AMOS software. Thirdly, on this basis, it verifies the influence of psychological capital of the new-generation entrepreneurs on entrepreneurial performance and the moderating effect of entrepreneurial environment perception. The results show that there is a significant positive correlation between the dimensions of psychological capital and entrepreneurial performance. Gender, age, educational background, marital status, the establishment time of enterprises, and the number of employees all have a significant impact on the psychological capital of the new generation of entrepreneurs. Among them, the psychological capital of the new generation of entrepreneurs aged 31 to 35 is the best, followed by aged 26 to 30, 21 to 25, and the worst is 20 years old and below, which is logical. The correlation coefficient between psychological capital and entrepreneurial performance, social capital and entrepreneurial performance shows a significant positive correlation. The research on the relationship between psychological capital, social capital and entrepreneurial performance of new-generation entrepreneurs systematically explains why some enterprises created by the new generation of entrepreneurs can achieve rapid growth, and deepen the research in related fields.